Foreigners and the City: An Historiographical Exploration for the Early Modern Period - Donatella Calabi (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper will focus on the physical traces left by different minorities in the European city of the early modern age. Looking to the urban context in the main important ports and commercial centers we can find violent conflicts, traditional uses, as well as new urban strategies by the governors to keep together (for economic and social purposes) city-dwellers and foreigners. The invention of specific buildings and the effect on the architectural language is often quite visible and a mean of cultural exchanges.
Keywords: 330; City; History of Architecture; Modern Age; Foreigners; Minorities